Nature+ Quantitative Baseline Household and Worker Survey, Viet Nam - International Food Policy Research Institute; Development and Policies Research Center (International Food Policy Research Institute, 2024)
In 2023, the Nature Positive Solutions (Nature+) baseline survey was conducted in Vietnam, focusing on the districts of Sa Pa and Mai Son. The study aimed to describe the socio-economic conditions and agricultural systems in these areas, providing a baseline assessment to inform ongoing Nature+ interventions. The survey covered 1,153 smallholder farmer households (858 treated and 295 control) across 23 villages. Data collection employed a two-stage sampling technique and assessed various variables, including socio-economic characteristics, agricultural practices, land use, nutrition, and adoption of Nature+ practices. This data will support the evaluation of Nature+'s impacts on inclusion, poverty reduction, food security, livelihoods, and environmental sustainability. Additionally, the survey included interviews with 334 workers, covering socio-demographic characteristics, contract types, forced labor, harassment, workplace health and safety, wages, and overtime. Furthermore, community-level data were collected through interviews conducted by the team’s supervisors in all 23 surveyed villages. Each discussion involved at least three community leaders as key informants.